2005
DOI: 10.1007/s00148-005-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Out of Africa: what drives the pressure to emigrate?

Abstract: Abstract.Who intends to leave Africa and what drives the pressure to emigrate? For four African countries (Ghana, Senegal, Morocco and Egypt) we evaluate the strength of push and pull factors in stating emigration intentions 'out of Africa'. In general, one can say that the typical potential migrant is young, male, optimistic about attaining a higher living standard and finding a job and having relatively modern values compared to those who intend to stay. Classical push factors like unemployment and poverty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 37 publications
(18 reference statements)
5
59
0
2
Order By: Relevance
“…Is it really true that the prospect of emigration stimulates education even for those who don't emigrate ex post? Surveys of emigrant intentions support this view: far more people express some intention to emigrate than actually do emigrate (Gibson and McKenzie, 2012;Van Dalen et al, 2005). A recent wave of research has investigated the underlying mechanisms at a more micro level.…”
Section: Brain Drain or Brain Gain?mentioning
confidence: 79%
“…Is it really true that the prospect of emigration stimulates education even for those who don't emigrate ex post? Surveys of emigrant intentions support this view: far more people express some intention to emigrate than actually do emigrate (Gibson and McKenzie, 2012;Van Dalen et al, 2005). A recent wave of research has investigated the underlying mechanisms at a more micro level.…”
Section: Brain Drain or Brain Gain?mentioning
confidence: 79%
“…First, mortality generally differs by sex (Kruger and Nesse 2007;Rogers et al 2010). Second, sex is a major selection factor in migration, and it is also implicated in the other selection factors (Cerrutti and Massey 2001;van Dalen et al 2005;Kley 2011). Third, sex is a significant indicator of the diminishing healthy immigrant effect (Cairney and Østbye 1999;Dunn and Dyck 2000;Setia et al 2011), with research showing that Canada's female immigrants are more likely to experience declining physical, mental health, and general health status than male immigrants (Newbold and Danforth 2003;Creatore et al 2010;Kim et al 2013).…”
Section: Resultsmentioning
confidence: 98%
“…In their analysis of what drives the pressure to emigrate out of Africa, economists van Dalen and colleagues (2005) assess the empirical evidence on the relationship between migration intentions and actual behavior to be encouraging. Supporting this conclusion, De Jong’s (2000) study in Thailand showed that intentions to migrate were strong predictors of more permanent actual migration behavior two years later, controlling for numerous micro-economic theory factors, such as human capital, household economy, local labor market, and demographic variables.…”
Section: Introductionmentioning
confidence: 99%